Isolation and test of novel yeast strains with lignin usage capability and phenolic compound resistance - Anaid Bautista‐Guerrero; Rene A. Lara‐Diaz; Valérie Pihen; Erick R. Bandala; Jose Luis Sanchez‐Sala (MicrobiologyOpen, 2022)
Abstract Five yeast fungi strains (i.e., two Cryptococcus albidus, one Candida guillermondii, and two Candida tropicalis) were isolated from sugarcane and tested for their use of lignin as sole carbon source and their potential to grow in the presence of phenol and phenol derivatives (i.e., pentachlorophenol and p‐nitrophenol). The full set of isolated yeasts showed ligninolytic activity, achieving at least 36% lignin degradation after 25 days. The C. albidus JS‐B1 strain had the highest ligninolytic activity, achieving 27% lignin degradation within 4 days. This increased activity was associated with the production of ligninolytic laccase enzymes. All the tested yeast fungi strains showed growth in the presence of high concentrations of phenolic compounds (i.e., 900 mg/L phenol, 200 mg/L p‐nitrophenol, 50 mg/L pentachlorophenol) and showed significant potential for lignin and lignin by‐product degradation. Each of these five strains has the potential to be used in biological treatment processes for contaminated effluents from paper pulping and bleaching or phenol and phenol‐derivative biodegradation processes for other industrial wastewater effluents.